2016
DOI: 10.1002/cbdv.201500292
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Volatile Emission of Different Aerial Parts of Caper (Capparis spinosa L.)

Abstract: We analyzed the spontaneous volatile emission of different aerial parts of the caper (Capparis spinosa L.) by HS-SPME-GC/MS. We identified 178 different compounds of which, in different proportions based on the sample type, the main ones were (E)-β-ocimene, methyl benzoate, linalool, β-caryophyllene, α-guaiene, germacrene D, bicyclogermacrene, germacrene B, (E)-nerolidol, isopropyl tetradecanoate, and hexahydrofarnesyl acetone. The multivariate statistical analyses seem to point out that the parameter leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In contrast, the noticeable abundance of (E)-b-ocimene (12), exclusive to the floral profile, underlines the major attractant action of the reproductive organs. The differences in volatile emissions based on the ecological role of the plant organs has also been reported for Capparis spinosa L., showing the importance of these compounds in the planthabitat relationship (Ascrizzi et al, 2016). Moreover, these authors reported (E)-b-ocimene as the main compound emitted in the floral headspace analysis, confirming the pollinatorattraction role hypothesized for this volatile in the present study (Ascrizzi et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, the noticeable abundance of (E)-b-ocimene (12), exclusive to the floral profile, underlines the major attractant action of the reproductive organs. The differences in volatile emissions based on the ecological role of the plant organs has also been reported for Capparis spinosa L., showing the importance of these compounds in the planthabitat relationship (Ascrizzi et al, 2016). Moreover, these authors reported (E)-b-ocimene as the main compound emitted in the floral headspace analysis, confirming the pollinatorattraction role hypothesized for this volatile in the present study (Ascrizzi et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…In a study investigating the spontaneous volatile emission of different aerial parts of C. spinosa , Ascrizzi et al [ 52 ] reported that 178 volatile organic compounds (VOCs) were determined by headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography (GC)/MS. The major VOCs emitted by leaves of C. spinosa were germacrene D (20%) and decanal (15%) [ 52 ]. The flower bud of C. spinosa mainly emitted isopropyl tetradecanoate (26%), ( E )-nerolidol (17%) and hexahydrofarnesyl acetone (11%) [ 52 ].…”
Section: Phytochemical Properties Of C Spinosamentioning
confidence: 99%
“…The major VOCs emitted by leaves of C. spinosa were germacrene D (20%) and decanal (15%) [ 52 ]. The flower bud of C. spinosa mainly emitted isopropyl tetradecanoate (26%), ( E )-nerolidol (17%) and hexahydrofarnesyl acetone (11%) [ 52 ]. For the fruits of C. spinosa , the majority of the VOCs were β-caryophyllene (40%), α-guaiene (12%), bicyclogermacrene (11%) and macrene B (8%) [ 52 ].…”
Section: Phytochemical Properties Of C Spinosamentioning
confidence: 99%
See 1 more Smart Citation
“…We collected species-VOC relationship data from the KNAp-SAcK metabolite ecology section of the KNApSAcK family databases [9]. We also collected additional data from different papers and journals using Google Scholar and other publication sites [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54]. The final data consists of 12,410 species-VOC relations including 710 species and 1,740 different VOCs.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%